Using Serological Proteome Analysis to Identify Serum Anti‐Nucleophosmin 1 Autoantibody as a Potential Biomarker in European‐American and African‐American Patients With Prostate Cancer. Issue 15 (15th July 2016) - Dai, Liping; Li, Jitian; Xing, Mengtao; Sanchez, Tino W.; Casiano, Carlos A.; Zhang, Jian‐Ying
Abstract : BACKGROUND: The prostate‐specific antigen (PSA) testing has been widely implemented for the early detection and management of prostate cancer (PCa). However, the lack of specificity has led to overdiagnosis, resulting in many possibly unnecessary biopsies and overtreatment. Therefore, novel serological biomarkers with high sensitivity and specificity are of vital importance needed to complement PSA testing in the early diagnosis and effective management of PCa. This is particularly critical in the context of PCa health disparities, where early detection and management could help reduce the disproportionately high PCa mortality observed in African‐American men. Previous studies have demonstrated that sera from patients with PCa contain autoantibodies that react with tumor‐associated antigens (TAAs). METHODS: The serological proteome analysis (SERPA) approach was used to identify tumor‐associated antigens (TAAs) of PCa. In evaluation study, the level of anti‐NPM1 antibody was examined in sera from test cohort, validation cohort, as well as European‐American (EA) and African‐American (AA) men with PCa by using immunoassay. RESULTS: Nucleophosmin 1 (NPM1) as a 33 kDa TAA in PCa was identified and characterized by SERPA approach. Anti‐NPM1 antibody level in PCa was higher than in benign prostatic hyperplasia (BPH) patients and healthy individuals. Receiver operating characteristic (ROC) curve analysis showed similar high diagnostic value for PCa in the test cohort (area under the curve (AUC):0.860) and validation cohort (AUC: 0.822) to differentiate from normal individuals and BPH. Interestingly, AUC values were significantly higher for AA PCa patients. When considering concurrent serum measurements of anti‐NPM1 antibody and PSA, 97.1% PCa patients at early stage were identified correctly, while 69.2% BPH patients who had elevated PSA levels were found to be anti‐NPM1 negative. Additionally, anti‐NPM1 antibody levels in PCa patients at early stage significantly increased after surgery treatment. CONCLUSION: This intriguing data suggested that NPM1 can elicit autoantibody response in PCa and might be a potential biomarker for the immunodiagnosis and prognosis of PCa, and for supplementing PSA testing in distinguishing PCa from BPH. Prostate 76:1375–1386, 2016 . © 2016 Wiley Periodicals, Inc.